Mapping of basketball courts in Kulon Progo Regency - Jati Satria Perdana; Muhammad Irvan Eva Salafi (Jorpres (Jurnal Olahraga Prestasi), 2026)
This study aims to map basketball court facilities in Kulon Progo Regency, covering availability, physical condition, and compliance with FIBA, PERBASI, and Permenpora standards. This quantitative descriptive study employed a survey method using total sampling on 35 courts that met the inclusion criteria. Data were collected through observation using a checklist covering 26 components across three aspects: court infrastructure, game equipment, and supporting facilities. Data analysis was descriptive, involving the calculation of scores, percentages, and categorization of suitability. The results showed: (1) The 35 courts are spread across 12 subdistricts with an uneven distribution; Wates Subdistrict accounts for 37.14%, while each of the five northern subdistricts has only one court; (2) Physical conditions are generally good (77.14% in the Good–Very Good category, 22.86% in the Fair category), but there are significant safety deficiencies: 91.43% of goalposts lack padding, 40% have substandard free space, and 42.86% lack lighting; (3) Ring height compliance is 100%, court dimensions 68.57%, free space 60%, and indoor lighting 5.71%. Conclusion: The availability and physical condition of the courts are generally good, but there are still disparities in distribution as well as deficiencies in safety and compliance with technical standards. Priority improvements are recommended for safety components and the equitable development of facilities to support the 2027 PORDA performance targets.